Formation of Highly Ordered Molecular Porous 2D Networks from Cyano‐Functionalized Porphyrins on Cu(111). Issue 59 (17th September 2020) - Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Steinrück, Hans‐Peter; Marbach, Hubertus
Abstract: We investigated the adsorption of three related cyano‐functionalized tetraphenyl porphyrin derivatives on Cu(111) by scanning tunneling microscopy (STM) in ultra‐high vacuum (UHV) with the goal to identify the role of the cyano group and the central Cu atom for the intermolecular and supramolecular arrangement. The porphyrin derivatives studied were Cu‐TCNPP, Cu‐ cis DCNPP, and 2H‐ cis DCNPP, that is, Cu‐5, 10, 15, 20‐tetrakis‐( p ‐cyano)‐phenylporphyrin, Cu‐ meso ‐ cis ‐di( p ‐cyano)‐phenylporphyrin and 2H‐ meso ‐ cis ‐di( p ‐cyano)‐phenylporphyrin, respectively. Starting from different structures obtained after deposition at room temperature, all three molecules form the same long‐range ordered hexagonal honeycomb‐type structure with triangular pores and three molecules per unit cell. For the metal‐free 2H‐ cis DCNPP, this occurs only after self‐metalation upon heating. The structure‐forming elements are pores with a distance of 3.1 nm, formed by triangles of porphyrins fused together by cyano‐Cu‐cyano interactions with Cu adatoms. This finding leads us to suggest that two cyano‐phenyl groups in the " cis " position is the minimum prerequisite to form a highly ordered 2D porous molecular pattern. The experimental findings are supported by detailed density functional theory calculations to analyze the driving forces that lead to the formation of the porous hexagonal honeycomb‐type structure. Abstract : Snowflake‐shaped porphyrins : Twelve doubly cyano‐functionalized Cu‐tetraphenylporphyrins form a snowflake‐like structure around a macropore, as observed by scanning tunneling microscopy at room temperature.